The Effectiveness of E-Learning Usage among University Students in the Kingdom of Saudi Arabia - Muberik, Sami (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Educational institutions have recently embraced e-learning systems, reflecting a modern trend in education that positively impacts the learning process. However, limited studies have investigated the impact of e-learning on higher education students and teaching staff during the COVID-19 pandemic, such as their experiences, lack of information on teaching and learning, and attitudes. This study, therefore, aims to fill this gap by evaluating the effectiveness of e-learning in university education. Employing a descriptive-analytical method, the study utilized a questionnaire to collect data from a sample of 5,876 students and 272 teachers at Imam Abdulrahman Bin Faisal University in Dammam, Eastern Province, Saudi Arabia. The results indicate that student satisfaction with e-learning is neutral, whereas faculty satisfaction is high. Additionally, faculty members possess the necessary knowledge and skills for e-learning. Given the variation in previous studies’ findings, the study recommends conducting further study to enrich the theoretical literature.